Understanding Agni: Physiological Significance in Ayurvedic Metabolism - Mishra, Avinash Kumar; Dash, Rajib Lochan (Journal of Neonatal Surgery, 2025)
In Ayurveda, Agni-the body’s metabolic fire-is fundamental to digestion, transformation, and tissue nourishment. This review delineates its complex nature, highlighting three primary types: JatharAgni, BhutAgni, and DhatvAgni. JatharAgni, located in the gastro-duodenal region, initiates the breakdown of food and governs the functionality of all downstream Agnis. Its state-from balanced (Samagni) to imbalanced modes such as VishamAgni, TikshnAgni, and MandAgni—directly influences metabolic efficiency and correlates with specific dosha-driven disorders. Following its action, BhutAgni, the elemental fires embedded in each of the five primordial elements, process digested food to match the body's own elemental makeup. Finally, seven DhatvAgni—each associated with one of the body’s tissues—ensure precise nutrient assimilation and tissue maintenance. Maintaining optimal Agni, especially JatharAgni, through proper diet and lifestyle is crucial for health, vitality, and longevity. Understanding its diverse manifestations underscores Ayurveda’s nuanced approach to metabolic regulation and disease prevention.